Nickel-copper-zinc ferrite material and preparation method thereof

By adjusting the elemental proportion of nickel copper zinc ferrite materials and adding toughening additives, the problem that existing ferrite materials are difficult to improve resistivity and toughness under high magnetic permeability is solved, and high-performance nickel copper zinc is achieved Ferrite material, suitable for miniaturized common mode inductors.

CN119504248APending Publication Date: 2025-02-25SHANDONG CHUNGUANG MAGNETOELECTRIC TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411616694.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

While the existing ferrite materials meet high permeability, it is difficult to improve resistivity and toughness at the same time, and there is a problem of core notch in the miniaturized common mode inductor.

Method used

By adjusting the elemental proportion of nickel copper-zinc ferrite materials, reducing iron content, increasing the proportion of ZnO and CuO, and adding toughening additives such as V2O5, MoO3 and Nb2O5 to control the grain size and element matching, and adopting appropriate sintering technology .

Benefits of technology

Nickel-copper-zinc ferrite material with high permeability, resistivity and toughness is suitable for network transformer common mode inductance and reduces the core notch rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005132413160000071
    Figure BDA0005132413160000071
Patent Text Reader

Abstract

The invention discloses a nickel-copper-zinc ferrite material and a preparation method thereof. The nickel-copper-zinc ferrite material comprises a main material and a toughening additive, wherein in terms of the total molar weight of the main materials being 100%, the main materials comprise 34%-48% of Fe2O3, 10%-12% of NiO, 5%-6% of CuO and the balance ZnO; the toughening additive is at least one of 300 to 1500 ppm of V2O5, 300 to 1000 ppm of MoO3 and 300 to 1000 ppm of Nb2O5 based on the total weight of the main materials being 100%. The preparation method comprises the following steps: (1) weighing the raw materials; (2) mixing the main materials, adding water, sanding, adding a polyvinyl alcohol solution, and carrying out spray granulation; (3) presintering and cooling; (4) adding a toughening additive, and sanding; and (5) adding a polyvinyl alcohol solution, and carrying out spray granulation, pressing and sintering to obtain the product. The nickel-copper-zinc ferrite material disclosed by the invention has the advantages of high magnetic conductivity, high resistivity, high toughness and the like, and is suitable for being applied to a common-mode inductor of a network transformer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ferrite materials, and more particularly to a nickel-copper-zinc ferrite material and a preparation method thereof. Background Art

[0002] With the continuous miniaturization and high power of ferrite materials and electronic devices, the demand for electronic components in today's electronic devices is becoming more and more diverse. In order to further reduce the size of electronic equipment, the form of network transformers has been gradually replaced by small common mode inductors instead of the original magnetic ring wire casing. At the same time, due to the reduction in size, the performance of ferrite materials is also required to be higher. The original magnetic permeability of the magnetic ring is required to be around 1000 (1K, 0.25mT), and now the magnetic permeability is required to be 2000 (1K, 0.25mT). At the same time, the working environment also has certain requirements for Curie temperature and withstand voltage. Therefore, it is necessary to solve the Curie temperature and withstand voltage problems of ferrite materials while maintaining high magnetic permeability.

[0003] To solve the voltage resistance problem of ferrite materials, it is necessary to improve the resistivity of ferrite materials. Usually, the Fe content in ferrite materials is reduced to solve the problem of Fe content in materials. 2+ However, after reducing the Fe content, the magnetic permeability and Curie temperature of the ferrite material will decrease. At the same time, after simply reducing the Fe content, the excess Cu content in the ferrite material will also lead to a decrease in the resistivity of the ferrite material. At the same time, the common mode inductor is small in size and the winding is thin, so the problem of wire scraping needs to be considered. The corners of the fired core need to be ground, but due to the current formula and sintering process of ferrite materials, it is easy to cause a core gap.

[0004] Therefore, how to obtain ferrite materials with high resistivity and high toughness while satisfying the magnetic permeability is a technical problem that people in this field need to solve urgently. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a nickel-copper-zinc ferrite material and a preparation method thereof, which has the advantages of high magnetic permeability, high resistivity, high toughness, etc., and is suitable for application in common-mode inductance of network transformers.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A nickel-copper-zinc ferrite material, comprising a main material and a toughening additive;

[0008] Among them, the total molar amount of the main material is 100%, and the main material is Fe 2 O 3 46%-48%, NiO10%-12% and CuO5%-6%, the balance is ZnO;

[0009] Based on the total weight of the main material as 100%, the toughening additive is V 2 O 5 300-1500ppm, MoO 3 300-1000ppm and Nb 2 O 5 At least one of 300-1000ppm.

[0010] In the present invention, Fe 2 O 3 Iron oxide is the largest raw material used in nickel-copper-zinc ferrites. It is used to react with NiO (nickel oxide), CuO (copper oxide) and ZnO (zinc oxide) to generate NiFe during the sintering process. 2 O 4 ,CuFe 2 O 4 and ZnFe 2 O 4 Ferrite.

[0011] V 2 O 5 Vanadium pentoxide is a low melting point substance that can produce a liquid phase at low temperatures, lower the initial temperature of the reaction, provide reaction nuclei, and promote the growth of small grains that wrap large grains, thereby increasing the elastic modulus of the nickel-copper-zinc ferrite material and resisting stress shock.

[0012] MoO 3 Molybdenum trioxide is a low melting point substance, which forms a liquid phase at 900°C, and can enable the nickel-copper-zinc ferrite material to be sintered under transitional liquid phase conditions, thereby increasing the density and thus improving the magnetic core strength of the nickel-copper-zinc ferrite material.

[0013] Nb 2 O 5 Niobium pentoxide is a common additive in nickel-copper-zinc ferrite. The appropriate addition can make the grains grow evenly to improve the magnetic permeability, density and resistivity of the ferrite material and significantly reduce the overall loss.

[0014] Further, based on the total molar amount of the main material as 100%, the main material is Fe 2 O 3 48.6%, NiO 12%, CuO 5.4% and ZnO 34%;

[0015] Based on the total weight of the main material as 100%, the toughening additive is V 2 O 5 500ppm, MoO 3 1000ppm and Nb 2 O 5 300ppm.

[0016] Further, based on the total molar amount of the main material as 100%, the main material is Fe 2 O 3 48%, NiO 10%, CuO 6% and ZnO 36%;

[0017] Based on the total weight of the main material as 100%, the toughening additive is V 2 O 5 500ppm and Nb 2 O 5 500ppm.

[0018] Further, based on the total molar amount of the main material as 100%, the main material is Fe 2 O 3 46%, NiO 11%, CuO 5% and ZnO 38%;

[0019] Based on the total weight of the main material as 100%, the toughening additive is V 2 O 5 1000ppm.

[0020] Furthermore, the above Fe 2 O 3 The Ca content is less than 300ppm, the Mn content is less than 2000ppm, the purity is higher than 99.6%, and the average particle size is less than 0.7μm.

[0021] The further beneficial effect of adopting the above is that the Fe selected by the present invention 2 O 3 The purity of Fe is relatively high, mainly to ensure that the molar ratio of the nickel-copper-zinc ferrite material meets the design formula and to ensure that the sintering temperature and performance of the nickel-copper-zinc ferrite material do not change significantly. 2 O 3 Higher Ca and Mn contents will affect the performance of NiCuZn ferrite materials and therefore need to be controlled.

[0022] A method for preparing a nickel-copper-zinc ferrite material comprises the following steps:

[0023] (1) Weighing each raw material according to the amount of the above nickel-copper-zinc ferrite material;

[0024] (2) Preliminarily mixing the main ingredients, then adding water to form a slurry, sand grinding, and finally adding a polyvinyl alcohol solution as a binder, spray granulation, and obtaining a granular material;

[0025] (3) pre-sintering the granular material, cooling it, forming a portion of ferrite, and obtaining a pre-sintered material;

[0026] (4) adding a toughening additive to the pre-sintered material, and sand-grinding to obtain a sand-grinded material;

[0027] (5) Add polyvinyl alcohol solution to the sand abrasive, spray granulate, press and sinter to obtain nickel-copper-zinc ferrite material.

[0028] Furthermore, in the above step (2), the solid content of the slurry is 50%-55%; the sand milling equipment is a sand mill, and the time is 15-45 minutes; the mass concentration of the polyvinyl alcohol solution is 8%-10%, and the added amount is 0.6%-2% of the mass of the slurry.

[0029] Furthermore, in the above step (3), the pre-firing equipment is a rotary kiln, the atmosphere is air, the temperature is 800-1050°C, and the time is 30-60min.

[0030] Furthermore, in the above step (4), the sand grinding equipment is a sand mill, the time is 60-150 min, and the sand grinding is performed to a particle size of 0.6-1.5 μm.

[0031] Furthermore, in the above step (5), the mass concentration of the polyvinyl alcohol solution is 8%-10%, and the amount added is 0.6%-2% of the mass of the abrasive; the pressing pressure is 6-10t / cm 2 , time is 1-5s, pressed to a density of 3.0-3.6g / cm 3 ; The sintering equipment is a muffle furnace, the atmosphere is air, the temperature is 1020-1200℃, the heating rate is 2-10℃ / min, and the holding time is 2-6h.

[0032] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:

[0033] The present invention reduces the iron content of the feed by adjusting the element ratio of the ferrite material, which can prevent the molar percentage of iron from exceeding 50% mol and causing Fe 2+ The Fe content is too low, which prevents the remaining Cu elements from being enriched on the surface of the core to reduce the interface resistance and thus the resistivity, thereby improving the resistivity of the ferrite material. At the same time, the grain size of the ferrite material is controlled to improve the magnetic permeability of the ferrite material. The element combination is controlled to ensure that the ferrite material has a high Curie temperature. Toughening additives are added to ensure the product qualification rate of the ferrite material. With the assistance of a suitable sintering process, a nickel-copper-zinc ferrite material with high magnetic permeability, high resistivity and high toughness is finally obtained, which can meet the application requirements of common-mode inductors of network transformers. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] In the following examples, Fe 2 O 3 The Ca content is 275ppm, the Mn content is 1980ppm, the purity is 99.6%, and the average particle size is 0.68μm.

[0036] Example 1

[0037] Nickel-copper-zinc ferrite material, including main material and toughening additive;

[0038] Among them, the total molar amount of the main material is 100%, and the main material is Fe 2 O 3 48.6%, NiO 12%, CuO 5.4% and ZnO 34%;

[0039] Based on the total weight of the main material as 100%, the toughening additive is V 2 O 5 500ppm, MoO 3 1000ppm and Nb 2 O 5 300ppm;

[0040] The preparation method of the nickel-copper-zinc ferrite material specifically comprises the following steps:

[0041] (1) Weighing each raw material according to the amount of the above nickel-copper-zinc ferrite material;

[0042] (2) The main ingredients are preliminarily mixed, then added to a sand mill, water is added to form a slurry with a solid content of 50%, sand milled for 30 minutes, and finally 0.5% polyvinyl alcohol solution with a mass concentration of 8.5% is added, spray granulation is performed, and granules are obtained;

[0043] (3) adding the pellets into a rotary kiln, pre-burning in an air atmosphere at 980° C. for 45 min, and cooling to obtain a pre-burned material;

[0044] (4) adding the pre-sintered material into a sand mill, adding a toughening additive, and sand milling for 120 min to obtain a sand abrasive with a particle size of 0.85 μm;

[0045] (5) Add 2% polyvinyl alcohol solution with a mass concentration of 8.5% to the sand abrasive, spray granulate, and granulate at room temperature at 8t / cm 2The pressure was pressed for 2s to obtain a density of 3.4 g / cm 3 The blank is placed in a muffle furnace, and in an air atmosphere, the temperature is first increased to 1100°C at a heating rate of 2°C / min, sintered for 3 hours, and then naturally cooled to room temperature to obtain a nickel-copper-zinc ferrite material with an average grain size of 22μm.

[0046] Example 2

[0047] Nickel-copper-zinc ferrite material, including main material and toughening additive;

[0048] Among them, the total molar amount of the main material is 100%, and the main material is Fe 2 O 3 48%, NiO 10%, CuO 6% and ZnO 36%;

[0049] Based on the total weight of the main material as 100%, the toughening additive is V 2 O 5 500ppm and Nb 2 O 5 500ppm;

[0050] The preparation method of the nickel-copper-zinc ferrite material specifically comprises the following steps:

[0051] (1) Weighing each raw material according to the amount of the above nickel-copper-zinc ferrite material;

[0052] (2) The main ingredients are preliminarily mixed, then added to a sand mill, water is added to form a slurry with a solid content of 52%, sand milled for 45 minutes, and finally 0.5% polyvinyl alcohol solution with a mass concentration of 10% is added, spray granulation is performed, and granules are obtained;

[0053] (3) adding the pellets into a rotary kiln, pre-burning them in an air atmosphere at 950° C. for 30 min, and cooling them to obtain a pre-burned material;

[0054] (4) adding the pre-sintered material into a sand mill, adding a toughening additive, and sand milling for 150 min to obtain a sand abrasive with a particle size of 0.8 μm;

[0055] (5) Add 1.5% polyvinyl alcohol solution with a mass concentration of 10% to the sand abrasive, spray granulate, and granulate at room temperature at 10t / cm 2 The pressure was pressed for 3s to obtain a density of 3.5g / cm 3 The blank is placed in a muffle furnace, and in an air atmosphere, the temperature is first increased to 1050°C at a heating rate of 10°C / min, sintered for 2 hours, and then naturally cooled to room temperature to obtain a nickel-copper-zinc ferrite material with an average grain size of 30μm.

[0056] Example 3

[0057] Nickel-copper-zinc ferrite material, including main material and toughening additive;

[0058] Among them, the total molar amount of the main material is 100%, and the main material is Fe 2 O 3 46%, NiO 11%, CuO 5% and ZnO 38%;

[0059] Based on the total weight of the main material as 100%, the toughening additive is V 2 O 5 1000ppm;

[0060] The preparation method of the nickel-copper-zinc ferrite material specifically comprises the following steps:

[0061] (1) Weighing each raw material according to the amount of the above nickel-copper-zinc ferrite material;

[0062] (2) The main ingredients are preliminarily mixed, then added to a sand mill, water is added to form a slurry with a solid content of 55%, sand milled for 30 minutes, and finally 0.5% polyvinyl alcohol solution with a mass concentration of 9% is added, spray granulation is performed, and granules are obtained;

[0063] (3) adding the pellets into a rotary kiln, pre-burning in an air atmosphere at 950° C. for 60 min, and cooling to obtain a pre-burned material;

[0064] (4) adding the pre-sintered material into a sand mill, adding a toughening additive, and sand milling for 120 min to obtain a sand abrasive with a particle size of 1.5 μm;

[0065] (5) Add 1% polyvinyl alcohol solution with a mass concentration of 9% to the sand abrasive and spray granulate it at room temperature at 6t / cm 2 The pressure was pressed for 5s to obtain a density of 3g / cm 3 The blank is placed in a muffle furnace, and in an air atmosphere, the temperature is first increased to 1150°C at a heating rate of 6°C / min, sintered for 6 hours, and then naturally cooled to room temperature to obtain a nickel-copper-zinc ferrite material with an average grain size of 20μm.

[0066] Performance Testing

[0067] The nickel-copper-zinc ferrite materials obtained in Examples 1-3 were respectively made into 25*15*10 standard rings, and their magnetic permeability was tested using an Iwasaki SY-8218B-H tester, their resistance was tested using a Tonghui TH2683 insulation resistance tester, and their withstand voltage was tested using a Tonghui TH9320 AC / DC withstand voltage insulation tester. At the same time, the core gap rate was tested when 100 cores were ground at the corners.

[0068] The test results are shown in Table 1.

[0069] Table 1 Performance test results of nickel-copper-zinc ferrite materials of Examples 1-3

[0070]

[0071] It can be seen from Table 1 that the magnetic permeability of the nickel-copper-zinc ferrite material of Examples 1-3 of the present invention can reach 1500-2200 (1K, 0.25mT), the Curie temperature can reach 110-125°C, the resistance on both sides of the mark ring can reach more than 1500GΩ, and it can withstand a voltage of 5000V without breakdown. At the same time, the core gap rate is less than 3.0% when the core corners are ground.

[0072] The above experiments show that the present invention reduces the iron content of the feed by adjusting the element ratio of the ferrite material, which can prevent the molar percentage of iron from exceeding 50% mol and causing Fe 2+ The Fe content is too low, which prevents the remaining Cu elements from being enriched on the surface of the core to reduce the interface resistance and thus the resistivity, thereby improving the resistivity of the ferrite material. At the same time, the grain size of the ferrite material is controlled to improve the magnetic permeability of the ferrite material. The element combination is controlled to ensure that the ferrite material has a high Curie temperature. Toughening additives are added to ensure the product qualification rate of the ferrite material. With the assistance of a suitable sintering process, a nickel-copper-zinc ferrite material with high magnetic permeability, high resistivity and high toughness is finally obtained, which can meet the application requirements of common-mode inductors of network transformers.

[0073] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A nickel-copper-zinc ferrite material, characterized in that: It includes main ingredients and toughening additives; Taking the total molar amount of the main materials as 100%, the main materials are Fe2O3 46%-48%, NiO 10%-12% and CuO 5%-6%, and the balance is ZnO; Based on 100% of the total weight of the main material, the toughening additive is at least one of V2O5 300-1500ppm, MoO3 300-1000ppm and Nb2O5 300-1000ppm.

2. A nickel-copper-zinc ferrite material according to claim 1, characterized in that: Taking the total molar amount of the main materials as 100%, the main materials are Fe2O3 48.6%, NiO 12%, CuO 5.4% and ZnO 34%; Based on the total weight of the main material being 100%, the toughening additives include 500 ppm of V2O5, 1000 ppm of MoO3 and 300 ppm of Nb2O5.

3. The nickel-copper-zinc ferrite material according to claim 1, characterized in that: Taking the total molar amount of the main materials as 100%, the main materials are Fe2O3 48%, NiO 10%, CuO 6% and ZnO 36%; Based on the total weight of the main material being 100%, the toughening additives are 500 ppm of V2O5 and 500 ppm of Nb2O5.

4. The nickel-copper-zinc ferrite material according to claim 1, characterized in that: Taking the total molar amount of the main materials as 100%, the main materials are Fe2O346%, NiO 11%, CuO 5% and ZnO38%; Based on the total weight of the main material being 100%, the toughening additive is 1000 ppm of V2O5.

5. A nickel-copper-zinc ferrite material according to any one of claims 1 to 4, characterized in that: The Fe2O3 has a Ca content lower than 300 ppm, a Mn content lower than 2000 ppm, a purity higher than 99.6%, and an average particle size lower than 0.7 μm.

6. A method for preparing a nickel-copper-zinc ferrite material, characterized in that: The specific steps include: (1) Weighing each raw material according to the amount of the nickel-copper-zinc ferrite material according to any one of claims 1 to 5; (2) Preliminarily mix the main ingredients, then add water to form a slurry, sand grind, and finally add a polyvinyl alcohol solution, spray granulate, and obtain a granular material; (3) pre-calcining the pelletized material and cooling it to obtain a pre-calcined material; (4) adding a toughening additive to the pre-sintered material, and sand-grinding to obtain a sand-grinded material; (5) Adding polyvinyl alcohol solution to the abrasive material, spraying granulation, pressing, and sintering to obtain the nickel-copper-zinc ferrite material.

7. The method for preparing a nickel-copper-zinc ferrite material according to claim 6, characterized in that: In step (2), the solid content of the slurry is 50%-55%; the sand grinding equipment is a sand grinder, and the time is 15-45 minutes; the mass concentration of the polyvinyl alcohol solution is 8%-10%, and the added amount is 0.6%-2% of the mass of the slurry.

8. The method for preparing a nickel-copper-zinc ferrite material according to claim 6, characterized in that: In step (3), the pre-firing equipment is a rotary kiln, the atmosphere is air, the temperature is 800-1050° C., and the time is 30-60 minutes.

9. The method for preparing a nickel-copper-zinc ferrite material according to claim 6, characterized in that: In step (4), the sand grinding equipment is a sand mill, the time is 60-150min, and the sand grinding is performed to a particle size of 0.6-1.5μm.

10. The method for preparing a nickel-copper-zinc ferrite material according to claim 6, characterized in that: In step (5), the mass concentration of the polyvinyl alcohol solution is 8%-10%, and the amount added is 0.6%-2% of the mass of the abrasive; the pressing pressure is 6-10t / cm 2 , time is 1-5s, pressed to a density of 3.0-3.6g / cm 3 The sintering equipment is a muffle furnace, the atmosphere is air, the temperature is 1020-1200°C, the heating rate is 2-10°C / min, and the insulation time is 2-6h.